Early morbidities following paediatric cardiac surgery: a mixed-methods study - Katherine L Brown; Christina Pagel; Deborah Ridout; Jo Wray; Victor T Tsang; David Anderson; Victoria Banks; David J Barron; Jane Cassidy; Linda Chigaru; Peter Davis; Rodney Franklin; et al. (National Institute for Health Research, 2020)
Background: Over 5000 paediatric cardiac surgeries are performed in the UK each year and early survival has improved to > 98%. Objectives: We aimed to identify the surgical morbidities that present the greatest burden for patients and health services and to develop and pilot routine monitoring and feedback. Design and setting: Our multidisciplinary mixed-methods study took place over 52 months across five UK paediatric cardiac surgery centres. Participants: The participants were children aged < 17 years. Methods: We reviewed existing literature, ran three focus groups and undertook a family online discussion forum moderated by the Children's Heart Federation. A multidisciplinary group, with patient and carer involvement, then ranked and selected nine key morbidities informed by clinical views on definitions and feasibility of routine monitoring. We validated a new, nurse-administered early warning tool for assessing preoperative and postoperative child development, called the brief developmental assessment, by testing this among 1200 children. We measured morbidity incidence in 3090 consecutive surgical admissions over 21 months and explored risk factors for morbidity. We measured the impact of morbidities on quality of life, clinical burden and costs to the NHS and families over 6 months in 666 children, 340 (51%) of whom had at least one morbidity. We developed and piloted methods suitable for routine monitoring of morbidity by centres and co-developed new patient information about morbidities with parents and user groups. Results: Families and clinicians prioritised overlapping but also different morbidities, leading to a final list of acute neurological event, unplanned reoperation, feeding problems, renal replacement therapy, major adverse events, extracorporeal life support, necrotising enterocolitis, surgical infection and prolonged pleural effusion. The brief developmental assessment was valid in children aged between 4 months and 5 years, but not in the youngest babies or 5- to 17-year-olds. A total of 2415 (78.2%) procedures had no measured morbidity. There was a higher risk of morbidity in neonates, complex congenital heart disease, increased preoperative severity of illness and with prolonged bypass. Patients with any morbidity had a 6-month survival of 81.5% compared with 99.1% with no morbidity. Patients with any morbidity scored 5.2 points lower on their total quality of life score at 6 weeks, but this difference had narrowed by 6 months. Morbidity led to fewer days at home by 6 months and higher costs. Extracorporeal life support patients had the lowest days at home (median: 43 days out of 183 days) and highest costs (£71,051 higher than no morbidity). Limitations: Monitoring of morbidity is more complex than mortality, and hence this requires resources and clinician buy-in. Conclusions: Evaluation of postoperative morbidity provides important information over and above 30-day survival and should become the focus of audit and quality improvement. Future work: National audit of morbidities has been initiated. Further research is needed to understand the implications of feeding problems and renal failure and to evaluate the brief developmental assessment. Funding: This project was funded by the NIHR Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 30. See the NIHR Journals Library website for further project information.